2023
DOI: 10.3390/diagnostics13172787
|View full text |Cite
|
Sign up to set email alerts
|

Post-Operative Modified All-Inside ACL Reconstruction Technique’s Clinical Outcomes and Isokinetic Strength Assessments

Ahmet Serhat Genç,
Nizamettin Güzel,
Ali Kerim Yılmaz
et al.

Abstract: Background and Objective: Anterior cruciate ligament (ACL) injuries are very common among the athletic population. ACL reconstruction (ACLR) performed because of these injuries is one of the procedures performed by orthopedic surgeons using different grafting methods. This study aims to compare the data related to post-operative 6-month isokinetic strength values, strength-related asymmetry rates, time parameters, and joint angle in athletes who underwent ACLR with the Modified All-inside (4ST) technique, on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The coronal LCL sign is defined as the appearance of the lateral collateral ligament (LCL) as a single coronal section after tibial anterior translation and internal rotation, which is associated with ACL insufficiency, and it is reported to be correlated with ACL ruptures [8]. This finding is present in the literature as a reflection of knee instability [10,[25][26][27]. In our study, this finding was evaluated in preoperative and postoperative MRIs, and it was observed that there was no significant change after the surgery in 88.2% of cases, with a substantial level of agreement (kappa coefficient: 0.749, p value < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The coronal LCL sign is defined as the appearance of the lateral collateral ligament (LCL) as a single coronal section after tibial anterior translation and internal rotation, which is associated with ACL insufficiency, and it is reported to be correlated with ACL ruptures [8]. This finding is present in the literature as a reflection of knee instability [10,[25][26][27]. In our study, this finding was evaluated in preoperative and postoperative MRIs, and it was observed that there was no significant change after the surgery in 88.2% of cases, with a substantial level of agreement (kappa coefficient: 0.749, p value < 0.01).…”
Section: Discussionmentioning
confidence: 99%